Method for promoting microorganisms to induce calcium carbonate deposition
By adding zinc sulfate to the culture medium during the microbial-induced calcium carbonate deposition process, the problems of insufficient urea hydrolysis and environmental pollution are solved, the deposition efficiency and production of calcium carbonate are improved, and environmentally friendly mineral generation is achieved.
Patent Information
- Application Number
- CN202510084065.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-20
AI Technical Summary
In the process of microorganism-induced calcium carbonate deposition, insufficient urea hydrolysis leads to waste of raw materials, and the NH+4 generated is prone to environmental pollution.
By adding zinc sulfate to the culture medium, the microorganisms that can induce calcium carbonate deposition are cultured to increase the deposition efficiency of calcium carbonate.
It effectively improves the deposition conversion rate of calcium ions during microbial mineralization, increases the amount of calcium carbonate produced, reduces environmental pollution, and the by-product generated is environmentally friendly calcium carbonate.
Smart Images

Figure CN119736232A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microbial mineralization and microbial carbon fixation, and in particular to a method for promoting microbial-induced calcium carbonate deposition. Background Art
[0002] Microbial induced calcium carbonate deposition (MICP) is a common biologically induced mineralization process with the characteristics of fast reaction speed, low environmental conditions, wide application range, and significant greenhouse gas emission reduction effect. It is widely used in many fields such as geology, civil engineering, water conservancy, and environment. The pathways of microbial induced carbonate deposition include urea decomposition, amino acid ammoniation, denitrification, reduction of dissimilatory sulfate bacteria, photosynthesis, and methane oxidation. This method can fix carbon dioxide in the form of carbonate minerals such as calcite, dolomite, and vaterite without causing harmful effects on the environment. Its mechanism of action also has important implications for mitigating the greenhouse effect, and can be applied to tailings fixation, sand consolidation, concrete repair, etc.
[0003] When the urease-producing microorganisms currently used induce calcium carbonate deposition and mineralization, the added urea cannot be fully hydrolyzed, resulting in a waste of raw materials. At the same time, the NH+4 produced is likely to cause new environmental pollution. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for promoting microbial-induced calcium carbonate deposition.
[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is: Provided is a method for promoting microbial induction of calcium carbonate deposition, which includes culturing microorganisms capable of inducing calcium carbonate deposition by adding a culture medium containing zinc sulfate, and contacting a mixture of the cultured microorganisms and the culture medium with a calcium source, thereby increasing the deposition efficiency of calcium carbonate.
[0006] Furthermore, the microorganism is a combination of one or more of Bacillus cereus or Serratia marcescens.
[0007] Furthermore, the concentration of zinc sulfate in the culture medium containing zinc sulfate is 0.02-0.06 g / L.
[0008] Furthermore, the concentration of zinc sulfate in the culture medium containing zinc sulfate is 0.04 g / L.
[0009] Furthermore, the calcium source in the calcium source solution is a combination of one or more of calcium acetate and calcium chloride.
[0010] Furthermore, the mixture of the cultured microorganisms and the culture medium is contacted with a calcium source and then continuously shaken at 30° C. for mineralization.
[0011] The invention also provides an accelerator for promoting microorganism-induced calcium carbonate deposition, and the accelerator comprises zinc sulfate.
[0012] The beneficial effects of the present invention are: The present invention adds zinc sulfate to the culture medium when culturing microorganisms capable of achieving mineralization, then adds the cultured bacteria and the culture solution containing zinc sulfate to the mineral source solution, and waits for the completion of mineralization. Compared with the conventional microbial mineralization method, the addition of zinc sulfate can effectively improve the deposition conversion rate of calcium ions in the mineralization system during microbial mineralization, increase the consumption of calcium ions, and produce more calcium carbonate.
[0013] Using zinc sulfate to cultivate microorganisms can quickly catalyze the carbon dioxide hydration reaction, prompting the rapid deposition of calcium carbonate, thereby accelerating the matrix consolidation process, which is suitable for occasions that require rapid repair. Secondly, microorganisms cultivated in a culture medium containing zinc sulfate increase the concentration of inorganic carbon in the matrix, promote the deposition of more calcium carbonate, and enhance the stability of the matrix. The by-product produced is mainly calcium carbonate, which is an environmentally friendly mineral. No other toxic by-products are produced, and no new pollution is generated to the soil. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The figure is a comparison of the mineralization results of Bacillus cereus cultured with zinc sulfate and the control; Figure 2 This is a comparison chart of the changes in calcium ion concentration during the mineralization process of Bacillus cereus cultured with zinc sulfate; Figure 3 This is a comparison of the mineralization results of Serratia marcescens cultured with zinc sulfate; Figure 4 This is a comparison chart of the changes in calcium ion concentration during the mineralization process of Serratia marcescens cultured with zinc sulfate; Figure 5 This is the X-ray detection image of the mineralization products of Bacillus cereus and Serratia marcescens; FIG6 is a scanning electron micrograph of the mineralization products of Bacillus cereus and Serratia marcescens; Figure 7 This is a picture taken of the sample prepared in Example 2; FIG8 is a stress variation diagram of Example 3; Fig. 9 is the XRD pattern of the sample prepared in Example 2; Fig.10 This is the SEM image of the sample prepared in Example 2. DETAILED DESCRIPTION
[0015] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0016] Example 1 In this example, Bacillus cereus ATCC 14579 purchased from the German Collection of Microorganisms and Cell Cultures GmbH (DSMZ) and Serratia marcescens ATCC 13880 purchased from the German Collection of Microorganisms and Cell Cultures GmbH were selected as experimental strains. After the experimental bacteria were inoculated on a solid plate and cultured at 30° C. for 24 hours, a single colony was picked and inoculated into a liquid culture medium for culture to obtain a bacterial solution for use.
[0017] The promotion culture medium is prepared according to the formula in Table 1. Table 1 includes a liquid culture medium and a solid culture medium. In specific implementation, either one of them can be selected.
[0018] Table 1
[0019] Prepare a calcium source solution. In this embodiment, calcium acetate solution is selected as the calcium source solution. 26.43 g of calcium acetate is weighed and dissolved in a beaker, and the volume is fixed to 1000 mL to obtain a calcium source solution with a concentration of 150 mmol / L for use.
[0020] Experimental group (BC0.04) was set up: 5 mL of cultured bacterial solution ATCC 14579, 200 mL of promotion liquid culture medium and 100 mL of calcium source solution were mixed and added to a conical flask and placed in an incubator at 120 rpm and 30°C for 120 h.
[0021] Experimental group (SM0.04) was set up: 5 mL of cultured bacterial solution ATCC 13880, 200 mL of promotion liquid culture medium and 100 mL of calcium source solution were mixed and added to a conical flask and placed in an incubator at 120 rpm and 30°C for 120 h.
[0022] A control group (BC0) was also set up: the difference between the control group (BC0) and the experimental group (BC0.04) was that zinc sulfate was not added to the 200 mL liquid culture medium, and the other proportions were consistent with the 200 mL promotion liquid culture medium; Set up a control group (SM0): The difference between the control group (SM0) and the experimental group (SM0.04) is that zinc sulfate is not added to the 200 mL liquid culture medium, and the other proportions are consistent with the 200 mL promotion liquid culture medium; In the culture, the Ca 2+ The concentration change trend is measured by: Determination of Ca in bacterial mineralization by EDTA (disodium ethylenediaminetetraacetic acid) method 2+ The concentration change trend is as follows: after centrifuging 5.0 mL of the mineralized solution, take the supernatant and place it in a 250 mL conical flask, add deionized water to dilute it to 100 mL, then add 2 mL of 20% triethanolamine solution and shake well, then add 5.0 mL of 10% NaOH solution and shake well, immediately add 2 drops of calcium indicator solution, control the amount to just be able to significantly see its color, and add EDTA standard solution until the solution changes from red to purple-blue. Measure the amount of EDTA standard solution used and use the following formula to calculate the Ca in the mineralized solution: 2+ concentration .
[0023] ; in, is the concentration of standard EDTA solution, mmol / L; is the volume of EDTA solution consumed, mL; is the volume of the mineralizing fluid, mL.
[0024] The results of the experimental group (BC0.04) and the control group (BC0) are shown in Figure 1 shown by Figure 1 It can be seen that after the addition of zinc sulfate, the amount of calcium carbonate mineralized by Bacillus cereus ATCC 14579 increased from 0.55243 g to 0.68523 g, and the overall efficiency increased by about 24.04%.
[0025] After 24 hours from the start of the mineralization experiment, the mineralization solution Ca was measured every 12 hours. 2+ The concentration was measured and the results were as follows Figure 2 As shown, Figure 2 (+) ZnSO4 is the experimental group (BC0.04), (-) ZnSO4 is the control group (BC0); Figure 2 It can be seen that during the 120-hour mineralization process, the calcium ion concentration of the mineralized solution of the experimental group (BC0.04) with the addition of zinc sulfate was always lower than that of the control group (BC0), and the calcium ion concentration curve of the experimental group (BC0.04) began to slow down after 120 hours of mineralization, while the calcium ion concentration curve of the control group (BC0) began to slow down after 100 hours of mineralization.
[0026] The results of the experimental group (SM0.04) and the control group (SM0) are shown in Figure 3 shown by Figure 3 It can be seen that after the addition of zinc sulfate, the amount of calcium carbonate mineralized by Serratia marcescens ATCC 13880 increased from 0.82873 g to 0.97137 g, and the overall efficiency increased by about 17.21%.
[0027] After 24 hours from the start of the mineralization experiment, the mineralization solution Ca was measured every 12 hours. 2+ The concentration was measured and the results were as follows Figure 4 As shown in the figure, the calcium ion decrease rate in the experimental group (SM0.04) with zinc sulfate added was faster, reaching the mineralization end point at around 72 hours, while the control group (SM0) without zinc sulfate added was around 96 hours. During the period of 70-80 hours, the microbial mineralization reaction reached the late stage, the nutrients in the system were basically exhausted, and the number of microorganisms reached the maximum number of microorganisms that the system could accommodate. At this time, all metabolic activities of the microorganisms were inhibited, the microbial mineralization reaction reached the end point, and the calcium ion concentration in the system remained basically unchanged.
[0028] The mineralized sediments of the experimental group (BC0.04) and the experimental group (SM0.04) were filtered, and the organic matter in the sediments was removed with 30% hydrogen peroxide, and then washed with distilled water. Finally, they were dried and ground with a mortar until there was no particle feeling. The phase composition of the mineralized product was determined by X-ray diffractometer. The results are as follows: Figure 5 The mineralization of the experimental group (BC0.04) and the experimental group (SM0.04) was detected using a scanning electron microscope, and the results are shown in Figure 6, where Fig. 6A The mineralization of the experimental group (SM0.04) Figure 6B This is the mineralization of the experimental group (BC0.04).
[0029] Depend on Figure 5 -6, it can be seen that the main phase composition of the mineralization product of Bacillus cereus ATCC 14579 is vaterite calcium carbonate, followed by calcite calcium carbonate. The main phase composition of the mineralization product of Serratia marcescens ATCC 13880 is vaterite calcium carbonate, and calcite calcium carbonate does not appear.
[0030] Example 2 The promoting liquid culture medium was prepared in the manner of Example 1, and a ringlet of Bacillus cereus ATCC 14579 was selected and inoculated into the seed liquid culture medium, and then cultured in a shaking incubator at 30 degrees Celsius and 120 r / min for 24 hours to prepare a seed liquid. Then, 1 mL was transferred from the seed liquid at an inoculum volume of 1% (v / v), inoculated into the promoting liquid culture medium, and then cultured in a shaking incubator at 30 degrees Celsius and 120 r / min for 24 hours to prepare a promoting bacterial liquid.
[0031] Take 100g of standard sand and put it into a 5.5×5.5cm mold for later use. Take 100mL of the cultured bacterial solution and 0.5M calcium acetate solution, mix them in a beaker, and inject them into the mold as described above with a plastic dropper. Inject once every 12 hours, cure in a 30℃ constant temperature incubator, and the curing cycle is 7 days. After curing, dry in a 60℃ oven. Remove the cured specimen from the mold and dry it for observation. Figure 7 As shown, Figure 7 A is loose sand before solidification, Figure 7 B is a mixed grouting solidification specimen. Before solidification, the specimen was dry loose sand. Figure 7 It can be seen that this method can solidify loose sand into a whole. The surface of the specimen is covered with a calcium carbonate deposition layer as thick as 4 mm. The specimen is well consolidated as a whole, with no obvious loose sand scattering phenomenon. A clearly visible microbial cementation layer is formed on the entire surface of the solidified specimen.
[0032] The sand used in the experiment is Xiamen standard sand (containing 99.8% quartz). This sand has uneven grading, grading coefficient Cu=6.4, curvature coefficient Cc=0.5, median particle size (D50) is 0.67mm, and the maximum dry density of dry loose sand is 1.478. The sand is soaked in 1M HCl solution before the experiment. When no bubbles are generated, it is repeatedly washed with deionized water 4-5 times and dried for use.
[0033] Example 3 Take the test piece prepared in Example 2, and set up a control group. The difference between the control group and Example 2 is that the seed liquid is inoculated in a liquid culture medium without zinc sulfate. A shear experiment is carried out on Example 2 and the control group, specifically: a ZJ strain-controlled direct shear apparatus is used, the sample is placed in a shear box, and shearing is performed at a shear rate of 0.8 mm per minute under a vertical pressure of 50 kPa. The hand wheel is rotated once to record the dynamometer reading until a peak value appears in the dynamometer reading, and the shearing is continued until the shear displacement reaches 4 mm. The shear strength takes the peak value in the shear displacement and shear stress diagram. If there is no peak value, the shear stress value at the shear displacement of 4 mm is taken. The size of the test piece is 61.8 mm in diameter and 20 mm in height. The initial cross-sectional area of the test piece is 30 m 2 , the dynamometer calibration coefficient is 1.87N / 0.01mm.
[0034] The stress variation diagram is obtained by statistical integration, and the result is shown in Figure 8. Fig. 8A is the stress change diagram of the control group. Figure 8Bis the stress change diagram of Example 2; as can be seen from Figure 8, both Example 2 and the control group show a trend of first rising and then falling. Since there is no calcium carbonate in the control group, the pores between the sand particles are large, and the obtained shear strength mainly comes from the interaction between the sand particles. Although there is calcium carbonate deposition inside Example 2, the distribution is uneven. When the specimen is subjected to stress, it immediately cracks into blocks, and some parts are in the form of loose sand. However, since the surface sand particles of Example 2 are coated with calcium carbonate, it still has a certain cohesive force.
[0035] Example 4 The test piece prepared in Example 2 destroyed in Example 3 was recovered and weighed to obtain the total weight of calcium carbonate and sand, recorded as m0. After adding sterile water to wash repeatedly 4 to 5 times, 1M hydrochloric acid was added for pickling. After no bubbles were generated, it was washed with sterile water, dried in an oven at 60°C, and weighed again to obtain the net sand weight, recorded as m1. The amount of calcium carbonate deposition was m c =m1-m0. The calculation shows that the calcium carbonate deposition in the specimen of Example 2 reaches 16.18g. Since the entire specimen is immersed in the deposition system, the entire process from chemical deposition to biological deposition after chemical deposition decomposition can be completed, and the loss of calcium carbonate is small. The maximum dry density of the specimen after curing is measured by the drainage method, and the maximum dry density of the cured specimen is 1.974.
[0036] Example 5 A small amount of the sample prepared in Example 2 destroyed in Example 3 was ground until there was no granularity, and an X-ray diffraction experiment was performed using a Japanese Rigaku D / max2200VPC X-ray diffractometer (XRD) with a diffraction angle of 3° to 80°. After obtaining the diffraction pattern, a powder diffraction card (PDF card) edited and published by the Joint Conference on Powder Diffraction Standards (JCPDS) was used for phase analysis to obtain the crystal form of calcium carbonate obtained by deposition. The XRD pattern is shown in FIG. Fig. 9 As shown by Fig. 9 It can be seen that quartz is the main component of the standard sand used in the experiment. By comparing with the standard card, it was found that calcite and vaterite calcium carbonate were generated in the solidified specimens.
[0037] Take small particles from the shear-damaged specimen and observe the bonding between sand particles, between sand particles and calcium carbonate particles, and between calcium carbonate particles in the solidified specimen under a high-low variable vacuum field emission scanning electron microscope. Fig.10 As shown by Fig.10It can be seen that the strain induced the formation of calcium carbonate after zinc sulfate culture, which was deposited in the gaps of the sand samples and attached to the surface of the sand samples. Most of the calcium carbonate is in the form of particles, and a small part is in the form of layered rhombuses. At the same time, bacterial pits left by the strain can be seen on the sediments. In the process of strain-induced calcium carbonate deposition, calcium carbonate crystals use mineralizing bacteria as nucleation sites and are deposited on the surface of sand particles and in the gaps between particles. The size of the calcium carbonate crystals gradually increases due to the continuous stacking of calcium carbonate crystals, which eventually leads to the cementation of calcium carbonate crystal particle clusters on the surface of adjacent sand particles, thereby achieving the cementation of the originally adjacent but non-contacting particles into a whole. The calcium carbonate crystals first fill the surface and then cement, thereby improving the integrity and strength of the sand sample.
Claims
1. A method for promoting microbial induction of calcium carbonate deposition, characterized in that: By adding a culture medium containing zinc sulfate, culturing microorganisms capable of inducing calcium carbonate deposition, and contacting a mixture of the cultured microorganisms and the culture medium with a calcium source, the deposition efficiency of calcium carbonate can be increased.
2. The method for promoting microbial induced calcium carbonate deposition according to claim 1, characterized in that: The microorganism is a combination of one or more of Bacillus cereus and Serratia marcescens.
3. The method for promoting microbial induced calcium carbonate deposition according to claim 1, characterized in that: The concentration of zinc sulfate in the culture medium containing zinc sulfate is 0.02-0.06 g / L.
4. The method for promoting microbial induced calcium carbonate deposition according to claim 3, characterized in that: The concentration of zinc sulfate in the culture medium containing zinc sulfate is 0.04 g / L.
5. The method for promoting microbial induced calcium carbonate deposition according to claim 1, characterized in that: The calcium source in the microbial mineralization process is a combination of one or more of calcium acetate and calcium chloride.
6. The method for promoting microbial induced calcium carbonate deposition according to claim 1, characterized in that: The mixture of the cultured microorganisms and the culture medium is contacted with a calcium source and then mineralized at 30°C.
7. An accelerator for promoting microbial-induced calcium carbonate deposition, characterized in that: The accelerator includes zinc sulfate.
Citation Information
Patent Citations
Method for preparing calcium carbonate by using catalysis of microbial carbonic anhydrase
CN102121033A
Method for researching sand soil solidification effects by carbonic anhydrase mineralization bacteria
CN109142092A
Rapid curing method for calcareous sand
CN115075221A
In situ precipitation of calcium carbonate (CaCO3) by indigenous microorganisms to improve mechanical properties of a geomaterial
US20110027850A1
Production of zinc sulphate concentrates from a dilute zinc sulphate solution
US20110165059A1